(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The Kingdom of Saudi Arabia stands out as the wealthiest and most significant nation in the Middle East. The researcher has been employed at the College of Business Administration in Prince Sattam bin Abdulaziz University, Al Kharj, since 2014. Annually, the college welcomes around three hundred students eager to pursue a business administration course. The researcher, responsible for teaching a grammar course, recognized that the students’ lives revolve closely around cars, mobiles, and football.